Institutional Arrangements for Financial Consumer Protection - World Bank Group (World Bank, Washington, DC, 2016)
There is growing evidence that financially inclusive countries are more financially stable and exhibit better micro- and macro-economic conditions conducive to financial well-being of individual consumers. In order to produce significant economic and societal benefits, financial inclusion needs to be promoted in an environment where it is safe for consumers to use financial services and products. Strong financial consumer protection (FCP) helps ensure that the growing use of financial services benefits consumers and does not create undue risks while also supporting financial stability, integrity, and inclusion objectives. Building upon the fifteen most recent World Bank diagnostic reviews and informed by key guidance and relevant research, this note deals exclusively with institutional arrangements for FCP that refer to the number, capacity, organization, structure, resources, and processes of the agency(ies) responsible for FCP regulation and supervision of financial institutions. Institutional arrangements are one of the key determinants of efficiency and ultimate success of any FCP framework. This note is intended to assist policymakers, regulators, and supervisors seeking to establish new institutional arrangements or strengthen the existing ones in their respective countries. The note discusses importance of FCP, main models around the world, their advantages and disadvantages, as well as principal challenges faced by FCP agencies.